Comparison of the left and right ventricular size and systolic function of low-risk fetuses in the third trimester: Which is more dominant? - Zhu, Chen; Li, Man; Xu, Cheng-Jie; Ding, Meng-Juan; Xiong, Yu; Liu, Rui; Ren, Yun-Yun (Frontiers in Cardiovascular Medicine, 2023)
Objective To quantify fetal cardiovascular parameters utilizing fetal-specific 2D speckle tracking technique and to explore the differences in size and systolic function of the left and right ventricles in low-risk pregnancy. Methods A prospective cohort study was performed in 453 low-risk single fetuses (28+0–39+6 weeks) to evaluate ventricular size [i.e., end-diastolic length (EDL), end-systolic length (ESL), end-diastolic diameter (ED), end-systolic diameter (ES), end-diastolic area, end-systolic area, end-diastolic volume (EDV), and end-systolic volume (ESV)] and systolic function [i.e., ejection fraction (EF), stroke volume (SV), cardiac output (CO), cardiac output per kilogram (CO/KG), and stroke volume per kilogram (SV/KG)]. Results This study showed that (1) the reproducibility of the interobserver and intraobserver measurements was good to excellent (ICC 0.626–0.936); (2) with advancing gestation, fetal ventricular size and systolic function increased, whereas right ventricular (RV) EF decreased and left ventricular (LV) EF was not significantly changed; (3) LV length was longer than RV length in diastole (2.24 vs. 1.96 cm, P < 0.001) and systole (1.72 vs. 1.52 cm, P < 0.001); (4) LV ED-S1 and ES-S1 were shorter than the RV ED-S1 and ES-S1 (12.87 vs. 13.43 mm, P < 0.001; 5.09 vs. 5.61 mm, P < 0.001); (5) there were no differences between the LV and RV in EDA or EDV; (6) the mean EDV ratio of right-to-left ventricle was 1.076 (95% CI, 1.038–1.114), and the mean ESV ratio was 1.628 (95% CI, 1.555–1.701); (7) the EF, CO and SV of the LV were greater than the RV (EF: 62.69% vs. 46.09%, P < 0.001; CO: 167.85 vs. 128.69 ml, P < 0.001; SV: 1.18 vs. 0.88 ml, P < 0.001); (8) SV and CO increased with ED-S1 and EDL, but EF was not significantly changed. Conclusion Low-risk fetal cardiovascular physiology is characterized by a larger RV volume (especially after 32 weeks) and greater LV outputs (EF, CO, SV, SV/KG and CO/KG).